A study on the glycoside content of Euphorbia hirta - Florentino, Susan Barican
The study dealt with the extraction and isolation of glycosides from gatas-gatas, scientifally known as E. hirta L. (Family Euphorbiaceae). The TLC and column chromatography was utilized to determine effective solvent system for the glycosides content of the plant studied.